Development of HIV drug resistance and therapeutic failure in children and adolescents in rural Tanzania: an emerging public health concern. (2nd January 2017) - Muri, Lukas; Gamell, Anna; Ntamatungiro, Alex J.; Glass, Tracy R.; Luwanda, Lameck B.; Battegay, Manuel; Furrer, Hansjakob; Hatz, Christoph; Tanner, Marcel; Felger, Ingrid; Klimkait, Thomas; Letang, Emilio
Abstract : Objective: To investigate the prevalence and determinants of virologic failure and acquired drug resistance-associated mutations (DRMs) in HIV-infected children and adolescents in rural Tanzania. Design: Prospective cohort study with cross-sectional analysis. Methods: All children 18 years or less attending the paediatric HIV Clinic of Ifakara and on antiretroviral therapy (ART) for at least 12 months were enrolled. Participants with virologic failure were tested for HIV-DRM. Pre-ART samples were used to discriminate acquired and transmitted resistances. Multivariate logistic regression analysis identified factors associated with virologic failure and the acquisition of HIV-DRM. Results: Among 213 children on ART for a median of 4.3 years, 25.4% failed virologically. ART-associated DRM were identified in 90%, with multiclass resistances in 79%. Pre-ART data suggested that more than 85% had acquired key mutations during treatment. Suboptimal adherence [odds ratio (OR) = 3.90; 95% confidence interval (CI) 1.11–13.68], female sex (aOR = 2.57; 95% CI 1.03–6.45), and current nonnucleoside reverse transcriptase inhibitor-based ART (aOR = 7.32; 95% CI 1.51–35.46 compared with protease inhibitor-based) independently increased the odds of virologic failure. CD4 + T-cell percentage (aOR = 0.20; 0.10–0.40 per additional 10%) and older age at ART initiation (aOR = 0.84 per additional year of age; 95% CI 0.73–0.97) were protective (also in predicting acquired HIV-DRM). At the time of virologic failure, less than 5% of the children fulfilled the WHO criteria for immunologic failure. Conclusion: Virologic failure rates in children and adolescents were high, with the majority of ART-failing children harbouring HIV-DRM. The WHO criteria for immunologic treatment failure yielded an unacceptably low sensitivity. Viral load monitoring is urgently needed to maintain future treatment options for the millions of African children living with HIV. Abstract : Supplemental Digital Content is available in the text